2015
DOI: 10.1007/s13165-015-0117-3
|View full text |Cite
|
Sign up to set email alerts
|

Production duality, profitability, driving forces and constraints in organic peanut cultivation in India

Abstract: Production duality in peanut cultivation is referred as conventional and organic method. A field survey was conducted in Gujarat state, India, to assess the cost and benefits of production duality in peanut; different organic formulations practised; and motivational factors and constraints in organic peanut cultivation. Thirty organic peanut growing and equal number of conventional farmers were selected through multistage sampling procedure, and face to face interview was conducted using pretested interview sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
0
0
2
Order By: Relevance
“…O ROI do investimento nos três cenários analisados é positivo e esse fato é reflexo do potencial da cultura do amendoim em gerar FCO positivos, o que torna a produção do amendoim operacionalmente viável para todas as estratégias de arrendamento utilizadas, isto é, a cada ano, o produtor consegue auferir mais receitas que os seus custos e despesas operacionais desembolsáveis. 875 474,827 476,787 478,754 480,729 482,711 484,701 486,698 488,703 490,536 270,238 270,238 270,238 270,238 270,238 270,238 270,238 270,238 270,238 270,238 202,637 204,589 206,549 208,516 210,491 212,473 214,463 216,460 218,465 OCF-positivity was also observed in India with net results of USD 534 per hectare and USD 536 per hectare for, respectively, organic and conventional peanut production (GOVINDARAJ et al, 2016). In Turkey, a study by Gözener (2018) also showed a net profit of USD 90.98 per hectare.…”
Section: Fonte: Elaborado Pelos Autoresunclassified
See 1 more Smart Citation
“…O ROI do investimento nos três cenários analisados é positivo e esse fato é reflexo do potencial da cultura do amendoim em gerar FCO positivos, o que torna a produção do amendoim operacionalmente viável para todas as estratégias de arrendamento utilizadas, isto é, a cada ano, o produtor consegue auferir mais receitas que os seus custos e despesas operacionais desembolsáveis. 875 474,827 476,787 478,754 480,729 482,711 484,701 486,698 488,703 490,536 270,238 270,238 270,238 270,238 270,238 270,238 270,238 270,238 270,238 270,238 202,637 204,589 206,549 208,516 210,491 212,473 214,463 216,460 218,465 OCF-positivity was also observed in India with net results of USD 534 per hectare and USD 536 per hectare for, respectively, organic and conventional peanut production (GOVINDARAJ et al, 2016). In Turkey, a study by Gözener (2018) also showed a net profit of USD 90.98 per hectare.…”
Section: Fonte: Elaborado Pelos Autoresunclassified
“…A geração de FCO positivos também foi observada na Índia com resultados líquidos de USD 534 por hectare e USD 536 por hectare, respectivamente, em produções orgânicas e convencionais de amendoim (GOVINDARAJ et al 2016). Na Turquia, o estudo de Gözener (2018) também demonstrou um lucro líquido de USD 90,98 por ha.…”
Section: Fonte: Elaborado Pelos Autoresunclassified